2006
DOI: 10.1038/sj.ejhg.5201711
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive intestinal peptide gene alterations in patients with idiopathic pulmonary arterial hypertension

Abstract: Pulmonary arterial hypertension is a progressive disease, characterised by increased proliferation of pulmonary artery smooth muscle cells, vasoconstriction and remodelling of the vascular wall leading to right heart failure and death. The idiopathic form is rare (idiopathic arterial primary hypertension (IPAH); formerly PPH, MIM# 178600). Our group correlated a deficiency in vasoactive intestinal peptide (VIP; MIM# 192320) levels in serum and lung tissue with the pathogenesis of IPAH. The aim of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
(14 reference statements)
0
11
0
Order By: Relevance
“…It was confirmed that IL8 is differentially expressed in colon cancer, and is associated with proliferation, migration, angiogenesis and chemosensitivity in colon cancer cell line models (30). The VIP gene has also been the focus of investigation in many studies ralating to human cancer (31)(32)(33)(34)(35)(36). WDR77, also known as p44, was reported to be related to the differentiation and proliferation in prostate epithelium (37).…”
Section: Discussionmentioning
confidence: 86%
“…It was confirmed that IL8 is differentially expressed in colon cancer, and is associated with proliferation, migration, angiogenesis and chemosensitivity in colon cancer cell line models (30). The VIP gene has also been the focus of investigation in many studies ralating to human cancer (31)(32)(33)(34)(35)(36). WDR77, also known as p44, was reported to be related to the differentiation and proliferation in prostate epithelium (37).…”
Section: Discussionmentioning
confidence: 86%
“…Knockout of VIP in the mouse produces a pulmonary hypertension phenotype that can be reversed by a 4-week infusion of VIP (Said et al, 2007). A polymorphism in the coding region of exon 7 (g.8129T4C) has been reported with a similar frequency distribution in Caucasians with and without PAH (50% vs 46%) (Haberl et al, 2007) but is perhaps more common in Chinese with PAH (40.7%) compared to controls (15.2%) (Y. . Serum VIP levels were numerically lower and pulmonary haemodynamics worse in the PAH patients with this variant (n=33) than those without (n=48), but the biological differences were only small, and so the clinical significance is uncertain(Y. .…”
Section: Vasoactive Intestinal Peptide (Aviptadil)mentioning
confidence: 99%
“…Knockout mice lacking the VIP gene or humans presenting polymorphism of sequences encoding VIP are affected by PAH, [17][18][19] as are patients with an underexpression of constitutive secretion of NO. 20 Thus, a diminution of VIP was expected; however, the measurement showed an unexpected and interesting increase.…”
Section: Figmentioning
confidence: 99%